Energy complexes are apparently associated with the switch-motor complex of bacterial flagella - Zarbiv, Gabriel; Li, Hui; Sourjik, Victor (Journal of molecular biology, 2012)
Recently, the switch-motor complex of bacterial flagella was found to be associated with a number of non-flagellar proteins, which, in spite of not being known as belonging to the chemotaxis system, affect the function of the flagella. The observation that one of these proteins, fumarate reductase, is essentially involved in electron transport under anaerobic conditions raised the question of whether other energy-linked enzymes are associated with the switch-motor complex as well. Here, we identified two additional such enzymes in Escherichia coli. Employing fluorescence resonance energy transfer in vivo and pull-down assays invitro, we provided evidence for the interaction of F0F1 ATP synthase via its β subunit with the flagellar switch protein FliG and for the interaction of NADH-ubiquinone oxidoreductase with FliG, FliM, and possibly FliN. Furthermore, we measured higher rates of ATP synthesis, ATP hydrolysis, and electron transport from NADH to oxygen in membrane areas adjacent to the flagellar motor than in other membrane areas. All these observations suggest the association of energy complexes with the flagellar switch-motor complex. Finding that deletion of the β subunit in vivo affected the direction of flagellar rotation and switching frequency further implied that the interaction of F0F1 ATP synthase with FliG is important for the function of the switch of bacterial flagella.
Available online: 19 December 2011
Gesehen am 30.10.2018